ANALYSIS OF THE INCIDENCE OF DENGUE FEVER (DHF) IN THE WORKING AREA OF THE TALANG UBI HEALTH CENTER, PALI REGENCY IN 2025 - Ni Putu Yanti; Nani Sari Murni; Gema Asiani; Yusnilasari; Indriany (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
The Dengue virus is a virus that can transmit disease, as its transmission is carried out by disease-carrying vectors, namely the Aedes aegypti and Aedes albopictus mosquitoes, through biting humans. The primary cause of the increase in DBD cases is the low level of DBD prevention behavior. There has been a fluctuation in the incidence of dengue fever in the service area of the Talang Ubi Health Center in PALI District, with 38 cases in 2022, increasing to 66 cases in 2023, and decreasing again to 43 cases in 2024. The objective of this study is to analyze the incidence of dengue fever (DBD) in the service area of the Talang Ubi Health Center. The research method used is analytical with a case-control study design. The study was conducted in the service area of the Talang Ubi Health Center in PALI District from April to May 2025. The research design was case-control. The population was 61,428 people living in the working area of Talang Ubi Health Center in PALI Regency. The sample was divided into 43 case group respondents and 43 control group respondents.  The case group was DHF patients in the working area of Talang Ubi Community Health Center in PALI Regency from January to December 2024. Meanwhile, the control group was people in the working area of the Talang Ubi Community Health Center of PALI Regency who were not diagnosed with Dengue Fever (DHF).  The sampling technique used was purposive sampling. Bivariate analysis used Chi-Square test, multivariate analysis used multiple logistic regression test, and univariate analysis was the first step in the data analysis process. The results showed the p value of knowledge 0.825, attitude 1.000. Water storage 0.004, garbage disposal system 0.093, home environmental conditions 0.093, cadre support 0, 049.  The conclusion is that there is a relationship between water reservoirs, garbage disposal systems, home environmental conditions and cadre support. The most dominant factor is the cadre support variable compared to other factors (OR 2.98). In preventing dengue fever cases, good cooperation between the community and health workers is essential in order to create a clean and safe environment that is free from such cases.